ION AND ENERGY HOMEOSTASIS IN PERIPHERAL BLOOD LYMPHOCYTES IN RATS AT DERMATITISES - Cheremisina, V.F. (World of Medicine and Biology, 2014)
We studied disorders of energy homeostasis and ion saponin-perforated peripheral blood lymphocytes in rats with dermatitis of various etiologies. Shown that stimulation of lymphocyte antigen triggers a cascade of energy-dependent processes, which lead to a redistribution of macroergs in the cell, and this is associated with a significant decrease oubain sensitive Na+,K+-АТР-ase and Ca2+,Mg2+-АТР-ase activity, a decrease in the pool of ATP in lymphocytes. Proved that with dermatitis of various etiologies, especially allergic nature, violated regulatory mechanisms in lymphocytes by overloading cells Na+ and Ca2+, which leads to energy deficit lymphocytes and a violation of their functional activity.